Research on Code-Division Multiple-Access of DS-SS/EBPSK Modulation - Peng Zhang; Lenan Wu (Dianxin kexue)
In order to realize multiple-access communication of direct sequence spread spectrum extended binary phase shift keying（DS-SS/EBPSK）modulation, a realization method based on code-division was researched. Firstly, based on the analysis of DS-SS/EBPSK modulation signal, the effective spread spectrum sequence which can be used for dispreading and code division multiple-access was obtained by formulizing the DS-SS/EBPSK modulation process. Then, the correlation receiver for DS-SS/EBPSK modulation signal detection was designed and the multiple-access transmission was realized by making use of the small-scale cross-correlation of different spread spectrum sequences. Finally, take m sequence for example, the relationship between bit error rate（BER） performance of the expected user and the number of users was simulated, so did the relationship between BER performance of the expected user and the cycle length of m sequence. The simulation results demonstrate the feasibility of the code-division multiple-access realization method and indicate that the interference degree depends on the cross-correlation of the spread spectrum sequences.